Analisis Perbedaan Efektivitas Organisasi ditinjau dari Kesesuaian, Kekuatan, dan Tipe Budaya - Retno hartati; Yunita Anggarini (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractThis study aims to identify and analyze how much influence the effectiveness of the organization’s culture is viewed from the standpoint of suitability, strength and type of culture in Higher Education institutions. Respondents in this study were 150 structural officials from 40 universities in Indonesia, which is taken by using purposive sampling method. The analysis shows that the three cultural variables have different influence on the effectiveness. Variable types of culture (especially Adhocracy culture) is seen to have the highest impact on the effectiveness of variables (scores F: 52 577, sign 0.000), compared with the strength of the cultural variables (scores F: 37 197, sign 0.000), and the variables that influence the cultural appropriateness minimum (no effect) on the effectiveness (scores F: .620, .432 sign)